2016
DOI: 10.1002/cncr.29886
|View full text |Cite
|
Sign up to set email alerts
|

Differences in marital status and mortality by race/ethnicity and nativity among California cancer patients

Abstract: Background It has been observed that married cancer patients have lower mortality rates than unmarried patients, but data for different racial/ethnic groups are scarce. The authors examined the risk of overall mortality associated with marital status across racial/ethnic groups and sex in data from the California Cancer Registry. Methods California Cancer Registry data for all first primary invasive cancers diagnosed from 2000 through 2009 for the 10 most common sites of cancer-related death for non-Hispanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 25 publications
(46 reference statements)
3
30
1
Order By: Relevance
“…Increasing tumor size, T stage and N stage, was related to the higher risk of NEN metastasis. Insurance and marital status had no influence on the metastasis of GI‐NENs to the liver, lung, bone and brain in the current study, although earlier reports showed that insured patients might receive more early examination and married patients tend to undergo earlier testing and receive more adequate treatment …”
Section: Discussioncontrasting
confidence: 74%
“…Increasing tumor size, T stage and N stage, was related to the higher risk of NEN metastasis. Insurance and marital status had no influence on the metastasis of GI‐NENs to the liver, lung, bone and brain in the current study, although earlier reports showed that insured patients might receive more early examination and married patients tend to undergo earlier testing and receive more adequate treatment …”
Section: Discussioncontrasting
confidence: 74%
“…Single patients are thought to have less support – emotionally, physically, or financially – and make different lifestyle choices, and these differences have an impact on their ability to survive a diagnosis of cancer [38]. Race or ethnicity may have some influence of the degree of risk for single patients, as Martinez et al [35] found that the risk of death due to cancer was greater for nonmarried white patients than for nonmarried black, Hispanic, or Asian/Pacific Islander patients. All of these issues should be examined in detail to find ways to help single patients experience better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect may not be as large as that of clinical factors, such as the histological type, our findings are supported by a growing body of knowledge that social and demographic factors, such as the marital status, can influence the survival of patients with cancer. Over the past 10 years, studies by multiple groups have revealed that the survival of married patients is significantly better than that of nonmarried patients for several types of cancer . Because the population we assessed was more than 80% White, the effect of marital status could be race‐specific.…”
Section: Discussionmentioning
confidence: 99%
“…Because the population we assessed was more than 80% White, the effect of marital status could be race‐specific. Recent studies by Martinez et al support this idea, because these authors found that race had a significant influence on the effect of marital status on all‐cause and cancer‐specific mortality among 800 000 patients in the California Cancer Registry (CCR) . The most viable explanations for the effect of marriage on survival are that married patients have more support (emotionally, physically, or financially) or are less likely to make lifestyle choices that are detrimental to their health .…”
Section: Discussionmentioning
confidence: 99%